Pengelolaan Badan Usaha Milik Desa (BUMDes) dalam Meningkatkan Perekonomian Desa - Maimunah Maimunah; Siti Aisyah; Nur Hidayah (Ideas Publishing, 2023)
Researchers still find BUMDes that are not managed properly, even though effective management can improve the community s economy. This study reveals the effectiveness of this management in improving the economy, supporting factors, and inhibiting factors. This research is a descriptive qualitative research with a system theory approach consisting of input, transformation process, and output. The findings of this study found that the input aspects of the use of raw materials, capital, and information sources have been implemented, but human resources and technology have not been implemented. In the aspect of transformation, work activities, management, use of technology, and operational methods have not been implemented. In the output aspect, the products and services produced are appropriate, but the financial results, information, and human resource products have not been implemented.